Error-processing abnormalities in pediatric anxiety and obsessive compulsive disorders. (29th June 2015) - Fitzgerald, Kate D.; Taylor, Stephan F.
<x content-type="archive" xml:space="preserve">Abstract</x> Anxiety and obsessive compulsive disorders are among the earliest occurring psychopathology and may derive from atypical maturation of neural networks for error processing. Psychological models have alternately suggested that over-detection of errors, excessive caring about errors, or failure of errors to elicit regulatory control could associate with the expression of anxiety. In this review article, the potential relevance of error processing for anxiety and obsessive compulsive disorders is described in the context of neurophysiological and functional magnetic resonance imaging (fMRI) research demonstrating altered brain response to errors in pediatric and adult patients. Finally, hypotheses about developmentally sensitive mechanisms of anxiety and obsessive compulsive disorders are drawn from the extant literature, and avenues for clinical translation are discussed.